DIFFERENTIAL REHABILITATIVE APPROACHES TO OSTEO ARTHRITIS OF KNEE-A CASE REPORT - NARESH BHASKAR RAJ (International Journal of Pharma and Bio Sciences, 2015)
Osteoarthritis is a degenerative joint disease. It affects the weight bearing joint. Osteoarthritis of knee and hip are very common amongst all the other forms of osteoarthritis.This case report explains the treatment of a patient who had symptoms and signs suggestive of osteoarthritis of knee. She complained of pain in both the knees, but more on the right side, early morning stiffness, difficulty in walking and limitation of functional activities. This case report emphasises the role of physical therapy in the rehabilitation of the patient with osteoarthritis of knee. This case report suggests that appropriate treatment techniques will prevent the worsening of the severity of the problem and also avoid or postpone the option of a surgical intervention.